African American Male College Athletes' Narratives on Education and Racism. (November 2016) - Singer, John N.
This study presents narrative case study vignettes of three elite African American male football athletes at a major historically White institution of higher education with a big-time athletics department. More specifically, I draw from critical race theory to garner insight into their secondary schooling background, what education means to them, and how racism impacts their holistic development. The focus group and individual interviews revealed each came from urban high schools in close proximity to the university, viewed education as more than classroom learning and obtaining a degree, and perceived racism as alive and well in college sport.